Efficacy and safety of OBI‐1, an antihaemophilic factor VIII (recombinant), porcine sequence, in subjects with acquired haemophilia A. (27th January 2015) - Kruse‐Jarres, R.; St‐Louis, J.; Greist, A.; Shapiro, A.; Smith, H.; Chowdary, P.; Drebes, A.; Gomperts, E.; Bourgeois, C.; Mo, M.; Novack, A.; Farin, H.; et al.
Summary: Acquired haemophilia A (AHA) is a rare bleeding disorder caused by autoantibodies against human factor VIII (hFVIII). OBI‐1 is an investigational, B‐domain deleted, recombinant FVIII, porcine sequence, with low cross‐reactivity to anti‐hFVIII antibodies. Efficacy can be monitored with FVIII activity levels in addition to clinical assessments. This prospective, open label, phase 2/3 study was designed to evaluate the efficacy of OBI‐1 treatment for bleeding episodes in subjects with AHA. After an initial dose of 200 U kg −1, OBI‐1 was titrated to maintain target FVIII activity levels, in correlation with clinical assessments, throughout the treatment phase. All 28 subjects with AHA had a positive response to OBI‐1 treatment 24 h after initiation despite inhibition of FVIII activity levels immediately after infusion in 10 subjects with baseline anti‐porcine FVIII inhibitors. Control of the qualifying bleed was ultimately achieved in 24 of 28 subjects. No related serious adverse events, thrombotic events, allergic reactions or thrombocytopaenia occurred. The results of this study indicate that OBI‐1 is safe and effective in treating bleeding episodes in subjects with AHA. The ability to safely and effectively titrate dosing based on FVIII activity levels in this study demonstrates that OBI‐1 fulfils the unmet medical need to monitor the key coagulation parameter in AHA patients.